2023
DOI: 10.1093/braincomms/fcad256
|View full text |Cite
|
Sign up to set email alerts
|

Effective connectivity between deep brain stimulation targets in individuals with treatment-resistant depression

Saba Amiri,
Mohammad Arbabi,
Milad Rahimi
et al.

Abstract: The therapeutic effect of deep brain stimulation on patients with treatment-resistant depression is strongly dependent on the connectivity of the stimulation region with other regions associated with depression. The aims of this study are to characterize the effective connectivity between the brain regions playing important roles in depression and further investigate the underlying pathophysiological mechanisms of treatment-resistant depression and the mechanisms involving deep brain stimulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Another one used a seed-to-voxel analysis where voxels within specific ROIs were considered in addition to ROI-to-ROI analyses (Jung et al, 2022). Three studies exclusively performed ROI-to-ROI analyses (Amiri et al, 2023;Gosnell et al, 2019;Poblete et al, 2022). Lastly, two studies opted for network analysis (Amiri et al, 2021;Zhu et al, 2019), which is a framework that envisions the brain as an intricate network.…”
Section: Connectivity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another one used a seed-to-voxel analysis where voxels within specific ROIs were considered in addition to ROI-to-ROI analyses (Jung et al, 2022). Three studies exclusively performed ROI-to-ROI analyses (Amiri et al, 2023;Gosnell et al, 2019;Poblete et al, 2022). Lastly, two studies opted for network analysis (Amiri et al, 2021;Zhu et al, 2019), which is a framework that envisions the brain as an intricate network.…”
Section: Connectivity Studiesmentioning
confidence: 99%
“…One study found that when DBS of the SCC was turned on, RSFC between the whole habenula and a cluster in the ACC was higher than when it was turned off (Elias et al, 2022). Another study, using dynamic causal modeling to model effective connectivity, provided evidence suggesting that in the left hemisphere, connections from the SCC to the habenula were excitatory in the TRD group, whereas they were inhibitory in HCs (Amiri et al, 2023). Overall, because of the great methodological diversity among the studies, no clear pattern emerges from these studies.…”
Section: Other Regionsmentioning
confidence: 99%